Pengembangan Sistem Manajemen Notulensi dan Dokumentasi Rapat Berbasis Web (Studi Kasus: Jurusan Teknik Informatika Fakultas Ilmu Komputer Universitas Brawijaya) - Ilyas Abdi Nugraha; Fajar Pradana; Achmad Arwan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
The meeting is part of an important activity of the civitas employee in the Faculty of Computer Science, Brawijaya University to negotiate or resolve a problem that concerns the common interest, or development of the Faculty. The thing that must be ready in meeting activities is to make the meeting agenda and make minutes of the meeting. Making minutes of the results of this meeting is important, to help the accreditation process or re-accreditation of study programs. But in the implementation found several problems. The first problem is that the flow of meeting event making is still done conventionally when notifying the meeting agenda by sending SMS to prospective meeting participants. If there are prospective meeting participants who are unable to attend, the meeting participants do not know the contents of the meeting because the meeting material is not accepted by meeting participants who are unable to attend. The absence of a meeting remainder automatically leads to a meeting making prospective meeting participants sometimes forget about meetings. The second problem, namely when making minutes of the meeting is still carried out by each meeting participant. So that many minutes of meetings are not archived and lost. This makes it difficult for the Quality Assurance Unit (UJM) to find minutes of meetings to meet the needs of accreditation or re-accreditation of study programs. The third problem is that during the implementation of the meeting it still involves volunteers from the meeting participants to document the meeting activities with photos or videos, but often the photos or videos are not archived because of forgetfulness. The development of this software is web based using the waterfall method. This system provides a meeting event remainder feature that uses the Google Calendar API. This system uses the Logitech C525 webcam. Unit testing is performed using the white-box testing method 3 times. Validation testing using the black-box testing method 52 times resulted in 100% valid. Usability testing using the System Usability Scale method produces a score of 76.6 which is categorized as acceptable, so that the system meets user needs.